The Role of Buzzers in Social Media in Guiding Public Opinion Regarding Political Choices - Jagad Aditya Dewantara; Syamsuri Syamsuri; Ayu Wandira; Afandi Afandi; Okti Hartati; Nurul Cahya; Putri Sapitri; T Heru Nurgiansah (JED (Jurnal Etika Demokrasi), 2022)
The use of social media platforms by various groups has made Buzzer known to social media users. The existence of a buzzer with all its advantages and disadvantages has become a phenomenon. The buzzer was originally just a person/individual who sells or/or services (product marketing), after that it was converted and used as a tool of power/authority holder (propaganda tool) to encourage and lead public opinion for certain purposes and people's political choices. Apart from this phenomenon, this study is intended to describe the contribution of the buzzer in the formation of people's views on social media. This study was carried out using a literature review research method that can support the text analysis method. From this study, it was found that the buzzer has a relevant contribution to the formation of public views on social media. At the same time in the creation and management of content or issues, the buzzer has a structured work hierarchy. Therefore, in responding to the presence of a buzzer, it should be viewed wisely. The conclussion is buzzer work does not run spontaneously, and cannot be separated from the wants and needs of a definite group.